Filling the gap: first confirmed record for the Ophisurus serpens (Anguilliformes: Ophichthidae) from the Anatolian coast of the South Aegean Sea. (11th May 2015) - Filiz, Halit; Ateş, Celal; Yapici, Sercan; Ağdamar, Sevan
Abstract : The occurrence of the rare serpent eel Ophisurus serpens is reported here for the first time from the Anatolian coasts of the South Aegean Sea. On 5 January 2015, a single specimen with a total length of 121. 2 cm and 363.14 g was collected by seine boat off Gökova Bay, Turkey. This finding shows that its population is expanding southwards, from Izmir to the Anatolian coasts of the Aegean Sea.